1996
DOI: 10.1210/endo.137.1.8536635
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of growth hormone on bone resorption and osteoclast differentiation.

Abstract: Although the actions of GH on osteoblasts have been extensively investigated, its effects on osteoclasts remain unknown. In the present study, the effects of GH on bone resorption and osteoclast differentiation were examined in vitro. Bovine GH (bGH; 1-100 ng/ml) significantly stimulated bone resorption by preexistent osteoclasts in stromal cell-containing mouse bone cell cultures, whereas it did not affect the bone-resorbing activity of isolated rabbit osteoclasts. When bGH was added to unfractionated bone ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 16 publications
4
44
0
5
Order By: Relevance
“…Drugs with high molecular weight cannot easily permeate through skin. Sometimes adhesives may not adhere well to all types of skin and maybe uncomfortable to apply (Nishiyama et al, 1996;Hsu et al, 2006).…”
Section: Side Effects Of Bps Therapymentioning
confidence: 99%
“…Drugs with high molecular weight cannot easily permeate through skin. Sometimes adhesives may not adhere well to all types of skin and maybe uncomfortable to apply (Nishiyama et al, 1996;Hsu et al, 2006).…”
Section: Side Effects Of Bps Therapymentioning
confidence: 99%
“…The presence of a functionally active specific IGF-Ir on mature osteoclasts supports a role for IGF-I in the activation of mature osteoclasts through the direct stimulation of local transmembrane receptors (Hou et al, 1997;Middleton et al, 1995). A binding site for IGF-I has been reported on hematopoietic blast cells (Nishiyama et al, 1996), which implies that IGF-I may directly stimulate the recruitment and formation of osteoclasts. It has been shown that IGF-I supports the activation and formation of osteoclasts and that osteoblasts mediate IGF-I-stimulated formation of osteoclasts (Slootweg et al, 1992;Mochizuki et al, 1992;Hill et al, 1995).…”
Section: Discussionmentioning
confidence: 64%
“…However, GH is able to stimulate mouse osteoclast-like cell formation from hemopoietic blast cells supported by GM-CSF (Nishiyama et al, 1996). The PCR product of mouse GHr was detected in these hemopoietic blast cells supported by GM-CSF, indicating a possible mechanism whereby GH may interact with osteoclast precursors and stimulate osteoclast-like cell formation (Nishiyama et al, 1996;Chihara and Sugimoto, 1997). 0.98 ± 0.14 4.2 ± 1.1 0.4 ± 0.4 2.0 ± 1.8 tl/tl + CSF-1 4 2.11 ± 0.3 8.7 ± 2.0*** 1.6 ± 1.2* 2.6 ± 0.9 * p < 0.05; *** p < 0.001.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, the hormone induces an increase in the markers of osteoblast differentiation, such as osteocalcin and alkaline phosphatase (Kassem et al 1993). GH is able to stimulate osteoclastic bone resorption through direct and indirect actions on osteoclast differentiation and through indirect activation of mature osteoclasts, possibly through local IGF-I/-II (Nishiyama et al 1996, Kanatani et al 2000.…”
Section: Introductionmentioning
confidence: 99%